2003
DOI: 10.1093/ortho/30.2.139
|View full text |Cite
|
Sign up to set email alerts
|

In vivoevaluation of two new moisture-resistant orthodontic adhesive systems: a comparative clinical trial

Abstract: The new moisture-resistant adhesive systems under study were found to be clinically efficient, though Assure exhibited a significantly higher bond failure rate than Unite and Transbond MIP. The higher frequency of adhesive failures observed with Assure might indicate a possible weak point at the adhesive-bracket interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 32 publications
1
16
0
3
Order By: Relevance
“…This is in accordance with the clinical studies conducted by Mavropoulos et al 20 and Pandis et al 21 Nevertheless, in the current investigation tooth type (incisor, canine and premolar) influenced the bond failure and survival rates with canine and premolar teeth demonstrating significantly higher failure rates and lower survival rates. Mavropoulos et al 20 observed that the bracket failure rate for posterior teeth (first and second premolars) was three times higher than the failure rate for anterior teeth (incisors and canine). Murfitt et al 13 reported considerable higher failures for the lower canines in the SEP group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in accordance with the clinical studies conducted by Mavropoulos et al 20 and Pandis et al 21 Nevertheless, in the current investigation tooth type (incisor, canine and premolar) influenced the bond failure and survival rates with canine and premolar teeth demonstrating significantly higher failure rates and lower survival rates. Mavropoulos et al 20 observed that the bracket failure rate for posterior teeth (first and second premolars) was three times higher than the failure rate for anterior teeth (incisors and canine). Murfitt et al 13 reported considerable higher failures for the lower canines in the SEP group.…”
Section: Discussionsupporting
confidence: 93%
“…[5][6][7] It was pointed out that the clinical use of SEPs in enamel-to-resin bonding has to be confirmed by clinical studies. 3 Several in vivo studies were published concerning the bond failure rates with CM and SEP. [8][9][10][11][12][13] In these studies the CM included etching with 37% phosphoric acid (15 or 30 seconds), primer application (Transbond MIP or XT) and bonding with Transbond XT light cure adhesive (20,40, or 60 seconds). SEP (Trans- bond Plus) was applied according to the manufacturer's instructions in these studies [8][9][10][11]13 except in one study.…”
Section: Introductionmentioning
confidence: 99%
“…Bond failure rates below 10% are generally considered clinically acceptable 14 . It is difficult to make a direct comparison between studies due to the variety of techniques, materials, research designs and trial durations 15 …”
Section: Discussionmentioning
confidence: 99%
“…No significant difference was found between SEP and CM, while significant differences were found between RMGI and each of SEP and CM. Mavropoulos et al [28] recommended that the accepted clinical bond failure rate is under 10%, so using SEP and CM in brackets bonding is considered clinically acceptable unlike RMGI. These findings can be explained by the difference in the mechanism of adhesion, which is a chemical one with RMGI while its micromechanical with the other groups [29].…”
Section: Discussionmentioning
confidence: 99%